Literature Review: Rencana Perawatan pada Gigi Anomali Anatomi Microdontia - Fauzan, Ahmad Ferza; Hartomo, Bambang Tri (Jurnal Kesehatan, 2021)
Microdontia is a tooth size abnormality that indicates a smaller than normal tooth size, it can also be accompanied by deformities, namely with a cone or cone shape. The role of restoration in dentistry must fulfill various aspects, namely aesthetic needs and functions. This literature aims to provide information and an overview of the selection of the right treatment for patients with microdontia anatomical anomalies. Denture crown treatment is expected to meet consumer satisfaction in terms of aesthetics, phonation and mastication. Denture crowns or crowns can be made of several materials, namely metal, composite, acrylic and porcelain, besides a combination of the two materials such as metal-porcelain or what is often called porcelain fused to metal (PFM). PFM is used to restore severe tooth decay to protect the remaining tooth tissue structure, maintain occlusion and provide aesthetic value.